The Use of Forward Chaining for Early Detection of Hepatitis B Risk Among Pregnant Women at Beber Community Health Center, Cirebon Regency - Yanto Haryanto; Maula Ismail (STIKes Budi Luhur Cimahi, 2026)
Hepatitis B virus (HBV) infection remains a major public health problem in Indonesia, particularly among pregnant women, where delayed detection may increase the risk of mother-to-child transmission as well as serious complications such as cirrhosis and hepatocellular carcinoma. The high cost of laboratory testing may contribute to delays in diagnosis and treatment. This study aimed to design a web-based early detection system for hepatitis B in pregnant women using the Forward Chaining method. A mixed-methods approach with a Research and Development (R&D) design was employed to develop and evaluate the system. The developed system was tested on 30 respondents and achieved a 100% success rate in black-box testing. Validation results showed a sensitivity of 100%, specificity of 90%, positive predictive value (PPV) of 82%, negative predictive value (NPV) of 100%, and an accuracy of 93%, indicating good diagnostic performance. The developed system can assist in the early detection of hepatitis B among pregnant women and may support earlier identification of the risk of mother-to-child transmission in primary healthcare settings.